HARMONIZATION OF PUBLIC AND PRIVATE INTERESTS IN TAXATION - KOLOMIIETS, GANNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The economic activity of the state largely depends on taxation. The formation of an effective tax policy within economic processes is one of the tools of state regulation of relations. The development of economic relations in the context of the growing processes of globalization forces world science and practice to look in a new way at understanding the traditional role of taxes and tax relations in the transitional economy. Tax relations between taxpayers and tax authorities have a direct impact on the economy as a whole. With the development of tax relations, the coordination of the interests of economic agents is of great importance, as their contradictory interaction based on feedback and self-organization is unpredictable. and, at the same time, contributes to the progressive development of society. The desire of the state to stabilize these processes (social, economic, political) leads to the need to find a compromise through state regulation and coordination of interests. Such harmonization of interests is mutually beneficial for both the state and business entities. As a result of the agreement, the state receives foreign capital, new forms of production, improvement of effective cooperation with suppliers and contractors, development of machinery and technology. Businesses, in turn, receive from the harmonious coordination of tax benefits, government guarantees, quality control, environmental friendliness, safety. The paper considers the nature of antagonistic interests of economic agents and the possibility of their coordination. The essence of coordination of public and private interests and their harmonization is investigated. The international experience of harmonization of interests in taxation for the purpose of its application in domestic practice is analyzed.